1993
DOI: 10.1111/j.1464-410x.1993.tb16249.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Blunt Renal Trauma

Abstract: The management of major renal lacerations after blunt trauma is still a matter of controversy. In this study, conservative treatment of major renal lacerations failed in 7 of 18 patients, leading to delayed surgery. Urography after blunt trauma was abnormal in 97% of patients with severe renal injury but a normal urogram did not exclude severe renal injury. Computed tomography had a greater degree of accuracy than urography and ultrasonography in determining the extent of the injury and was more practical to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 21 publications
0
33
1
3
Order By: Relevance
“…In two large series, [29,30] there was a 98% success rate for TPND, with a 5.6-6% complication rate in patients with urinary obstruction or urinary fistulae in an emergency setting. Although urinary extravasation and urinoma have been a relative indication for surgical approach [7,31], we do not consider that urinary extravasation alone, with no haemodynamic instability, obstruction or expanding urinoma, warrants initial surgery in these children. Kase et al [32] suggested that expectant management of blunt renal trauma might be reliable if the patient is stable, even if there is rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In two large series, [29,30] there was a 98% success rate for TPND, with a 5.6-6% complication rate in patients with urinary obstruction or urinary fistulae in an emergency setting. Although urinary extravasation and urinoma have been a relative indication for surgical approach [7,31], we do not consider that urinary extravasation alone, with no haemodynamic instability, obstruction or expanding urinoma, warrants initial surgery in these children. Kase et al [32] suggested that expectant management of blunt renal trauma might be reliable if the patient is stable, even if there is rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Los defensores del tratamiento quirúrgico inmediato 21,22 aducen que el tratamiento conservador se asocia a una elevada incidencia de hemorragias secundarias. Además el urohematoma puede infectarse dando lugar a la formación de abcesos u organizarse produciendo la compresión de la vía urinaria con ureterohidronefrosis secundaria, atrofia renal o hipertensión arterial, incrementándose pues la tasa de complicaciones tanto precoces como tardías.…”
Section: Discussionunclassified
“…[1][2][3][4] The kidneys are the most frequently injured organs when genitourinary system injuries are considered, and renal injury is recorded in approximately 1-5% of all the injuries. [5,6] Clinical findings are not manifest in 25% of the cases with a serious renal injury. [7] Although N-acetyl-β-D glucosaminidase (NAG; 2-acetamidodeoxy-β-glucoside acetamidodeoxy glucohydrolase) has been used for the identification of renal diseases and injuries, its application in renal traumas remains an unknown issue.…”
Section: Resultsmentioning
confidence: 99%